Utilization of E-Learning in Optimizing Madrasah Al-Quran and Al-Hadith Learning - Choirul Anam; Evi Fatimatur Rusydiyah (Jurnal Pendidikan Islam Indonesia, 2021)
The purpose of this study was to determine the use of madrasah e-learning in optimizing the learning of al-quran hadith for Class VII students of MTsN 1 Bojonegoro. The research design used in this study includes field research. With a qualitative research approach. This research was conducted at MTsN 1 Bojonergoro. Data collection techniques in this study used structured and in-depth interviews regarding optimizing the use of e-learning madrasas in al-quran hadith subjects and data analysis in this study using interactive models, data reduction, drawing conclusions and verification. While the results of this study used madrasah e-learning at MTsN 1 Bojonegoro has been running optimally for implementing distance learning. The problem that occurs in learning using E-learning was on the internet network and the quota must be sufficient for students and teachers because sometimes students and teachers who live in remote areas and did not have internet quotas were very difficult to access. so that quota assistance was needed for students and teachers so that learning using e-learning continues to run optimally.